Litter size and seasonality in reproduction for Guianan rodents and opossums. (2nd January 2019) - Catzeflis, François M.; Lim, Burton K.; Da Silva, Claudia Regina
ABSTRACT: We studied the litter sizes of small rodents and opossums caught in the Guianan Region (Brazilian Amapá, French Guiana, Suriname, and Guyana) by pooling the data of animals collected during various field trips conducted primarily between 1990 and 2017. A series of 569 counts of embryos (or of pouch young for marsupials) in 40 species of Didelphidae (N = 12 species), Sigmodontinae (18), Murinae (2), and Echimyidae (8) allowed for a more detailed characterization of the reproductive condition of 14 species known each by more than 10 pregnant females. For eight species with at least 20 pregnant females, an examination of seasonality in breeding occurrence documented that the two months with the lowest percentage of pregnant females are July and August (16.0 and 17.3%, respectively) during the end of the long wet season and beginning of the dry season. By contrast, January and February showed the highest abundance of pregnancies (57.9% and 55.8%, respectively) during the beginning of the long wet season. This timing coincides with most juveniles foraging during the height of the wet season in May when food is presumably most prevalent.